State regulation of demand in the market of tourist services - Shein, E. S.; Shein, Oleksii; Pererva, P. G. (Полтавський державний аграрний університет, 2023)
It has been proven that the development of tourism in Ukraine generates a new, very dynamic form of consumer demand, which with the movement of the consumer from the place of permanent residence, and even with the growth of the economic standard of living of the population. These factors play an extremely important role in the development of demand for tourist goods and services.
Державне регулювання попиту на ринку туристичних послуг
Keywords: demand; tourism business; partners; clients; factors; services